2022
DOI: 10.32598/jpr.10.1.986.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Iranian Neonatal Prematurity Minimum Data Set (IMSPIMDS): A Systematic Review Using Focus Group Discussion and the Delphi Technique

Abstract: Background: Information systems help to collect information about patients. The minimum data set (MDS) provides the basis for decision-making. Objectives: This study was conducted to determine the comprehensive national MDS for prematurity information management system (IMSPIMDS) in Iran. Methods: This research is a cross-sectional study with three steps including systematic review, focus group discussion, and Delphi technique. A systematic review was conducted in relevant databases. Then a focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Reviewed studies indicated that there was no significant difference in clinical outcomes such as mortality, BPD, IVH, NEC, ROP, sepsis, and oxygen therapy before and after using the mobile application ( 2 , 36 ). Moreover, there was no significant difference in perinatal mortality between the intervention and control group by using a mobile application ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewed studies indicated that there was no significant difference in clinical outcomes such as mortality, BPD, IVH, NEC, ROP, sepsis, and oxygen therapy before and after using the mobile application ( 2 , 36 ). Moreover, there was no significant difference in perinatal mortality between the intervention and control group by using a mobile application ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight is one of the most important indicators of community health and one of the main causes of infant mortality ( 1 , 2 ). Preterm refer to the neonates who are born before 37 complete weeks of pregnancy and due to the low birth weight, as well as the complications associated with preterm birth, newborns with these conditions are considered high-risk ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature birth is caused by several factors, such as premature rupture of the amniotic sac or membrane, maternal infection during pregnancy, and special economic and social conditions, which is the second underlying cause of death in children under 5 years (44%) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 About 120 million babies are born worldwide each year, about 25 million of whom are underweight at birth, and the proportion is about 50 percent in some parts of Asia. 3 According to statistics reported each year, an average of 32 million low birth weight infants is born in low income countries, of which two-thirds of cases belong to Asia. 4 The World Health Organization (WHO) has also reported a 10% prevalence of low birth weight in Iran.…”
Section: Introductionmentioning
confidence: 99%